Creating the 'classless' author: authorship and the social hierarchy, 1660–1800. Issue 9 (21st October 2019) - Hudson, Nicholas
ABSTRACT: This essay addresses the following question: 'What is the social class of the author?' Previous scholarship on the rise of modern authorship in the eighteenth century has generally answered this question in two different ways. According to some scholars, the 'author' emerged during this period in order to articulate and propagate 'bourgeois' ideology. According to other scholars, however, capitalist society increasingly excluded the literary artist from its governing aims and values. In revisiting this issue, I trace the emergence of the modern author from the late seventeenth to the eighteenth century. Beginning with the first literary biographies or 'lives of the poets' after the restoration, I argue that the problem of defining the author's social status became problematic during the debates over literary property in the eighteenth century. It was left to authors and critics of the late century to define a space for authorship separate from the emergent social hierarchy. Authorship became a distinct hierarchy with its own rules of ranking. Only in this 'classless' function could the author serve the officially endorsed role of providing a unifying social vision and harmonising the divisions generated by capitalism itself.